Faktor-faktor yang Memengaruhi Insiden Miopia Pada Siswa Sekolah Menengah Atas di Kota Padang - Martga Bella Rahimi; Yanwirasti Yanwirasti; Kemala Sayuti (Jurnal Kesehatan Andalas, 2015)
Abstrak Miopia merupakan kelainan refraktif yang paling banyak ditemukan di dunia. Hampir 90% miopia terjadi di negara berkembang. Berbagai faktor diduga berhubungan dengan insiden miopia seperti jenis kelamin, indeks masa tubuh (IMT), aktivitas dekat (dengan atau tanpa layar), aktivitas jauh (dengan atau tanpa layar), sosioekonomi, orangtua menderita miopia, serta riwayat kelahiran prematur atau berat badan lahir rendah (BBLR). Tujuan penelitian ini adalah menentukan hubungan antara faktor-faktor tersebut dan insiden miopia pada siswa Sekolah Menengah Atas(SMA) di Kota Padang. Penelitian dilakukan pada siswa SMA di Kota Padang yang berusia 15-17 tahun, dengan desain case-control study, population based dengan jumlah sampel 140 orang, yang terdiri dari 70 orang untuk kelompok kontrol dan 70 orang untuk kelompok kasus. Dikelompokkan setelah menguji ketajaman visus. Kemudian dilanjutkan dengan pengukuran tinggi badan, berat badan, serta pengisian kuesioner. Selanjutnya, data diolah dengan uji statistik chi-square. Aktivitas dekat dengan layar, IMT dan aktivitas jauh dengan layar merupakan faktor dominan yang memengaruhi insiden miopia pada siswa SMA di Kota Padang. Dibuktikan juga bahwa jenis kelamin, sosioekonomi, orangtua menderita miopia, riwayat lahir prematur ataupun BBLR tidak  memengaruhi insiden miopia. Kesimpulan penelitian ini adalah ada hubungan positif antara faktor risiko dengan insiden miopia.Kata kunci: miopia, faktor risiko, pelajar SMAAbstract Myopia is the most common refractive error in the world. Almost 90% of myopia patients are found in the developing countries. There are several factors suspected to be related to the incidence of myopia, such as gender, body mass index, close-range activities (with or without screen), distance activities (with or without screen), socioeconomic state, history of myopia in parents, and history of prematurity or low birth weight. The objective of this study was to determine the relation of those factors and the incidence of myopia on senior high school students in Padang city.This study was conducted on senior high school students in Padang city aged 15-17 years old. This study used population based case control design with 140 samples, consisted of 70 students for the control group and 70students for the case group. The process of data collection was conducted by initially classifying the respondents into case or control group using visual acuity test. It was followed by measuring body height and weight and filling the questionnaire.  Finally, those data were analyzed by using the chi square statistic test.The result of this study proved that the close-range activities with screen, were the dominant variable influencing myopia in senior high school students in Padang city, followed by BMI and distance activities with screen. It was also proved that none of thegender, socioeconomic state, history of myopia in parents, and history of prematurity or low birth weight have any influence toward myopia incidence. Conclusion of this study is that a positive correlation between suspected factors with myopia incidence. Keywords: myopia, risk factors, high school students